Longitudinal BMI percentile curves by maturity status of Japanese children - Mino, Tsutomu; Malina, Robert M.; Nariyama, Koichi (Anthropological Review, 2012)
The objective of the research was to prepare longitudinal percentile curves for the BMI (kg/m2) relative to time before and after peak height velocity (PHV) in Japanese boys and girls born between 1989 and 1991. Stature and weight were measured in every April from 6.5 to 16.5 years for 283 boys and 480 girls. Age at PHV was estimated by the proportional allotment method. The 50th percentile curves for the BMI of Japanese boys and girls born between 1989 and 1991 were similar to the corresponding curves for Japanese boys and girls born between 1972 and 1974. However, the 97th percentiles of children born between 1989 and 1991 were higher and the corresponding 3rd percentiles were lower compared to children born between 1972 and 1974. The differences can be attributed to the influence of early maturing children born between 1989 and 1991 on the 97th percentiles and of late maturing children born between 1989 and 1991 on the 3rd percentiles. The results highlight the need to consider the timing of maturity, in this case, age at PHV, when interpreting the BMI of adolescents.